Gold(I)‐Catalyzed Addition of Silylacetylenes to Acylsilanes: Synthesis of Indanones by CH Functionalization through a Gold(I) Carbenoid. (21st September 2015) - González, Jairo; Santamaría, Javier; Ballesteros, Alfredo
Abstract: A gold(I)‐catalyzed synthesis of indanones from trimethylsilylacetylenes and acylsilanes is presented. The reaction is initiated through a synergistic acylsilane activation–gold acetylide formation and involves consecutive alkyne σ‐gold(I) addition, π‐activation, and 1, 2‐migration of a silyl group. Studies performed on the reaction mechanism allowed to establish the nature of the silyl migrating group and invoke the participation of a gold(I) carbenoid intermediate. The reaction is completed by a gold(I) CH functionalization step.